Red-letter Reading Days: An eye-tracking perspective on Dr Seuss’ Green Eggs and Ham - Bergh, Luna; Beelders, Tanya (Revija za elementarno izobraževanje, 2023)
This article examines eye gaze while a multimodal text with vibrant and colourful images is read and furthermore specifically investigates the effect of the Stroop test on eye gaze. The Stroop colour-word test was designed to test the ability of a reader to suppress a habitual response. This particular variation of the test presented readers with words that refer to colour, but are presented in a different colour. Results indicate images are used when unfamiliar objects are referred to and faces and characters attract attention. The use of incongruent colours definitely causes cognitive dissonance and negatively affect reading.